Conjugation of the EEU and the “Belt and Road” initiative - Bukonkin, Dzianis A. (Journal of the Belarusian State University. International Relations, 2020)
The article is devoted to possible advantages and risks from the conjugation of the two integration projects: the EEU and the “Belt and Road” initiative. The author concludes that building a new type of relationship has considerable benefits but also poses challenges to the two projects. This problem exists primarily due to the different logic inherent in the two initiatives. While the EEU project is designed to protect and develop the economies of the member states of the union, the “Belt and Road” initiative implies absence of barriers and free movement of Chinese goods and investments around the world, which requires free trade zones around the world. China still seeks bilateral agreements with particular countries of the EEU, rather than interaction with the bodies of the integration bloc as a whole. The author gives a number of recommendations which, in his opinion, will help to avoid a number of risks and challenges and will contribute to the harmonious conjugation of the two ambitious projects.